2010
DOI: 10.1097/mcg.0b013e3181b4b68b
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Asian Americans After Treatments for Hepatocellular Carcinoma

Abstract: HBV and Hepatitis C were associated with over 90% of HCC cases in Asian Americans. HCC detected by surveillance identified more patients eligible for surgical and loco-regional therapies, which improved the overall and disease free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
1
25
1
Order By: Relevance
“…17 Cumulative data derived from Asian population with HCC revealed that elevation of ALP was associated with poor outcome. 9,10,18,19 This has been suggested in four previous studies; the first cohort study of 254 patients with HCC with no cirrhosis, ALP was found to be one of the independent prognostic factors for recurrence. 10 In another study of 218 patients with HCC and cirrhosis, ALP, tumor size (2 cm), multiplicity, and vascular invasion were found to be independent predictors for overall survival.…”
Section: Discussionmentioning
confidence: 61%
“…17 Cumulative data derived from Asian population with HCC revealed that elevation of ALP was associated with poor outcome. 9,10,18,19 This has been suggested in four previous studies; the first cohort study of 254 patients with HCC with no cirrhosis, ALP was found to be one of the independent prognostic factors for recurrence. 10 In another study of 218 patients with HCC and cirrhosis, ALP, tumor size (2 cm), multiplicity, and vascular invasion were found to be independent predictors for overall survival.…”
Section: Discussionmentioning
confidence: 61%
“…However, the role of these HBV mutations in hepatocarcinogenesis remains to be elucidated. Our observation of higher platelet counts in HCC patients who presented with larger tumors has been described previously but its cause is unknown [7]. Surveillance for HCC is an important issue in patients at high risk for developing HCC.…”
Section: Discussionmentioning
confidence: 66%
“…The exception is Japan, where hepatitis C virus (HCV) is linked to 70% while HBV is detected in 15% of HCC patients [5]. In the United States, HCV is associated with 50% of cases HCC in Caucasians, but HBV remains as the main etiologic agent in Asian Americans with HCC [6][7][8]. In the United States, Asian Americans have the highest mortality rates from HCC when compared to other ethnic groups [9].…”
Section: Introductionmentioning
confidence: 98%
“…0.0001). GGTP [16][17][18][19] and ALKP levels [20][21][22][23][24] have previously been reported to have prognostic significance in HCC patients. Thus, for the same size grouping (tercile I), the patients with higher AFP had increased levels of GGTP, ALKP, and total bilirubin, and lower serum albumin levels, showing worse liver function with high AFP and thus putatively a more aggressive HCC phenotype, reflected in their worse survival.…”
Section: Discussionmentioning
confidence: 99%